Perancangan Klaster Sistem Penguji Kode Program Menggunakan Docker - Ferdi Cezano Santosa; Mahendra Data; Heru Nurwarsito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Automated source code evaluation system is a system used to examine a program, in fact its research has been around since 1965. As technology grows, more and more people use Docker to create this system. By using Docker, system will be isolated so it can make computer safe. That's why the automated evaluation system in this study uses Docker to make sure the computer is safe. Even though the system can run safely, there are still some problems occurred on the automated system. The problem is how to make the evaluation process efficient and less burdening the computer and how to speed up the evaluation process if there is a program that takes a long time to be evaluated. Therefore, this research will make a cluster of automated source code evaluation system. In this cluster, there will be two instances, a master that divides the task and slaves that run the evaluation. Master and slaves will be connected with RPC because master will only call a function on the slave. The division of tasks will use round-robin algorithm, where slaves will be selected interchangeably. The test results show that this cluster capable of evaluating programs and able to evaluate up to 104 programs at once. In addition, this cluster can also divide the task efficiently so it can reduce the burdens on the computer and speed up the evaluation if the program takes a long time to be evaluated.